Some Scientific Bases for the Development of Undergraduate Fashion Design Training Programme Based on Comparative Education - Nguyen, Xuân Trà; Diep, Phương Chi (Journal of Technical Education Science, 2023)
The Fashion Design programmes at different universities in Vietnam lack the relative consistency because it is not based on in-depth study of job description profiles. Using the method of theoretical research with the approach of comparative education, the article analyzes and compares 25 profiles describing the profession Fashion Design in developed countries provided on websites, combined with the analysis of the compatibility level of the training programmes at 08 prestigious universities in Vietnam compared with the typical tasks in the field of Fashion Design. On that basis, the article discusses the theoretical concepts which orientate the development of training programme in the field of Fashion Design with the identification of 07 typical tasks that must be required for a Fashion Designer. Besides, the article makes recommendations on the necessary learning contents as the initial foundation for the curriculum framework of this field. Different universities can adapt from this basic framework in combination with local business needs and their own education philosophies to develop their own distinctive programme.